Fitohormonas citoquininas y giberalinas en el crecimiento vegetativo de los rebrotes axilares y retoños del híbrido de piña (Ananas comosus L. Merr.) MD2 - Terreros Coello, Dheyler Euclides (2017)
This research was carried out in the hacienda "Tierra Verde" belonging to the company PIÑAS RICAS DEL ECUADOR S.A. located in Km 9 ½ of the Quevedo - El Empalme road, in pineapple plantations (Ananas comosus L. Merr.) Golden Sweet hybrid or MD2 in the nursery stage. The field work had a duration of 12 weeks, from April to June 2017. The objective was to study the effect of cytokinins and giberalins on the vegetative development and propagation of sprouts and shoots of the hybrid of pineapple MD2 to identify the dose and phytohormone that generates greater sprouting, weight and height in the hijuelos. We used a completely randomized design with four replicates in a two-factor arrangement of two types of hormones with three doses (Low, medium and high) in addition to an absolute control, leaving a total of seven treatments. The variables under study were subjected to the Duncan significance test (P <0.05) for 15, 30 and 60 days after application, among which we have: Weight, height and shoot production. In the results achieved by the weight variable, a statistical significance (P <0.05) in the interaction A x B and of the control versus the rest at 30 and 60 days of treatment three, cytokinin at medium dose (Cytokin 1.5 mL./ Liter of water), where the highest average occurred at 30 days, whose value was 592.11 g. of weight of the pellet, surpassing the control. In the variable height of the sprouts, it indicated a significant difference (P <0.05) in the interaction of T3 (cytokinin - medium dose) with 63.96 cm. of height at 30 days after application of growth regulators. Statistical significance (P <0.05) was found in the production variable for the control versus the remainder at 15 days and in the interaction A x B shown at 30 days, in which the T7, giberalin at high dose (NewGibb 0.75 g. / Liter of water) obtained an average yield of 14.75 sprouts compared to the values obtained by the control, which was 7.25 per 40 plants, in turn at 15 days the highest production average was recorded with 18.00 sprouts. Giberalin at high dose (T7) caused the highest sprouting, giving a total of 201 sprouts for every 160 plants in the first three months of nursery. The phytohormone with high effectiveness in the increase of weight and height was the cytokinin at medium dose (T3), in addition, it turned out to be the most profitable treatment in the production of pineapple seed.